(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
As the pace of garbage production worldwide is worrying. Among these waste items include rubber, glass, wood goods, and plastic, among others. Compared to other waste materials, glass garbage is produced more often in India. However, approximately 60% of glass trash is either disposed of in landfills or stored in warehouses around the nation due to the low market value of recycled glass and expensive transit costs. The chemical inconsistencies among the many types of glasses, as well as the difficulties in separating different coloured glasses, make recycling challenging in addition to the existence of waste products such plastic caps, metals, and paper. However, in recent years it has become more difficult to replace coarse aggregate, sand, and gravel with waste glass in concrete and mortar. Since the 1960s, a number of researchers have investigated the use of waste glass larger than 4.75 mm as a coarse aggregate spare in concrete. There is a high need for aggregate and clay (brick) sources in the manufacturing of concrete. In 2015, 48.3 billion tonnes of aggregates were used annually as building materials worldwide, with 2.2 billion tonnes of them being used in India. Waste resources can be used as various types of construction material to get around the aggregate glass ultimatum. Only 45% of the 21 billion tonnes of glass trash produced in India in 2019 were recycled, demonstrating the necessity for effective waste glass procurement and management. This review provides examples of how leftover glass may be used to make building pieces. The study’s primary goals are to learn more about the physical and mechanical characteristics of waste glass-based blocks and other products, to generate sustainable building materials that can replace aggregates and clay, and to lessen the amount of waste glass dumped in landfills.